5(x-2)+3=-3(2x+1)-6

Simple and best practice solution for 5(x-2)+3=-3(2x+1)-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x-2)+3=-3(2x+1)-6 equation:


5(x-2)+3=-3(2x+1)-6

We simplify the equation to the form, which is simple to understand
5(x-2)+3=-3(2x+1)-6

Reorder the terms in parentheses
+(+5x-10)+3=-3*(2x+1)-6

Remove unnecessary parentheses
+5x-10+3=-3+*(+2x+1+)-6

Reorder the terms in parentheses
+5x-10+3=+(-6x-3)-6

Remove unnecessary parentheses
+5x-10+3=-6x-3-6

We move all terms containing x to the left and all other terms to the right.
+5x+6x=-3-6+10-3

We simplify left and right side of the equation.
+11x=-2

We divide both sides of the equation by 11 to get x.
x=-0.18181818181818

See similar equations:

| 7m+20-10=-25 | | 36r^2-60r+25=0 | | 15y-(-5y+36)=24 | | 12+x+9=37 | | x^2-6x-y^2+7=0 | | -98y^2-26=0 | | x+15+19=41 | | 40x+35y=720 | | 9aq^4-9an^4=0 | | 4y-(2y+2)=18 | | 21+20+x=70 | | 6/6-5/6 | | 49x^2-490x+697+16y^2+128y=0 | | k^3+20k^2+100k=0 | | 0.6x-0.6(5-x)=1.2 | | 2(x-10)+6(x-2)=48 | | 3ct^4-3cj^2=0 | | 4x(5+2)=22 | | -9=15+b-3 | | 1/200/30 | | 100=800b+5 | | 3-(-6)+(-7)+(-4)= | | 6(m+8)+2m=35-5m | | 20v^2-39vd+18d^2=0 | | log(d)=0.44 | | (s/14)=p | | 7+42x=21x+(13) | | 5x-3=-8x+10 | | -23u^2+34=-32u^2+32 | | 2-(-4)+(-7)= | | u=4(7n+35)+7(n+1) | | 3ln(x-1)=-3 |

Equations solver categories